Nurturing Self-Learning Strategies at CIEX Language Courses: Thesis design - Brito, Tomás; Castillo, Maria (CIEX JOURNAL, 2017)
This article presents the design of a Master’s thesis in Language Teaching and Applied Linguistics whose main research objective is to explore the students enrolled in the language courses at CIEX, self-study habits, their academic performance and the self-study practices recommended by the specialists in the areas of the thesis. In this paper, the elements of the design of the thesis are specified, being those of the background of the study. The statement of the problem, the main research objective, the main research question, the subsidiary research questions, the specific research objectives, the justification, the delimitations, and the research strategy are presented in this work. The literature review, the research method, the results, and the conclusions of the thesis will be presented in other future research articles.